2005
DOI: 10.1080/01140671.2005.9514374
|View full text |Cite
|
Sign up to set email alerts
|

Apricot (Prunus armeniaca) pollen morphological characterisation through scanning electron microscopy, using multivariate analysis

Abstract: Pollen grains of 11 Iranian apricot (Prunus armeniaca) cultivars were examined, using scanning electron microscopy (SEM). Pollen was collected in the 2002 growing season from mature apricot trees grown in The Apricot Collection Orchard, Ismailabad Horticultural Research Station, Qazvin, Iran. For SEM evaluation, pollen grains were observed and photographed at 1000× for whole grain and at 10 000× for sectioning of exine pattern (surface topography). The length (L) and the width (W) of grain, L/W ratio, distance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 17 publications
1
13
0
2
Order By: Relevance
“…Our data agreed with those reported by Evrenosoğlu & Misirli [4] for pollen size and for P/E ratio mean value in peach and almond and for the diameter of perforations in almond; concerning the width of muri in peach, moreover, they obtained similar values to those shown by Gilani et al [30]. The average pollen length and width, as well as P/E and the width of muri mean value in P. armeniaca, obtained in our study, are similar to the data observed by Arzani et al [31], while Gilani et al [30] reported similar range value as to DM (distance between muri) and WM. Otherwise, from the observations on almond from Iran reported by Vadafar et al [32], pollen grains of P. dulcis s.l.…”
Section: Discussionsupporting
confidence: 91%
“…Our data agreed with those reported by Evrenosoğlu & Misirli [4] for pollen size and for P/E ratio mean value in peach and almond and for the diameter of perforations in almond; concerning the width of muri in peach, moreover, they obtained similar values to those shown by Gilani et al [30]. The average pollen length and width, as well as P/E and the width of muri mean value in P. armeniaca, obtained in our study, are similar to the data observed by Arzani et al [31], while Gilani et al [30] reported similar range value as to DM (distance between muri) and WM. Otherwise, from the observations on almond from Iran reported by Vadafar et al [32], pollen grains of P. dulcis s.l.…”
Section: Discussionsupporting
confidence: 91%
“…U novije vreme, determinacija više genotipova vrsta roda Prunus na osnovu morfološke karakterizacije polenovih zrna obavljena je kod kajsije (Arzani et al, 2005;Asma, 2008), višnje (Miaja et al, 2000) i badema (Sorkheh et al, 2008). Autori se uglavnom slažu u pogledu ocene da razlike u morfologiji polena i ornamentaciji egzine meĎu sortama voćaka postoje, ali i da ove razlike često nisu velike.…”
Section: Biologija Oplođenja I Pomološke Osobine Novointrodukovanih Sunclassified
“…Oblik polenovih zrna vrsta roda Prunus opisan je kao zarubljen do eliptičan kod badema (Sorkheh et al, 2008), cilindričan kod breskve i šljive (Evrenosoğlu i Misirli, 2009), eliptičan ili zatupljeno-trouglast kod kajsije (Arzani et al, 2005). Odnos dužine i širine polenovih zrna sorti trešnje analiziranih u našem radu, ukazuje na njihov nešto izduženiji oblik (perprolate, Punt et al, 2007), u odnosu na ostale vrste roda Prunus -subprolate (Evrenosoğlu i Misirli, 2009) ili prolate-perprolate kod kajsije (Arzani et al, 2005), prolate-perprolate kod badema (Sorkheh et al, 2008) …”
Section: Biologija Oplođenja I Pomološke Osobine Novointrodukovanih Sunclassified
“…The investigations of the morphological peculiarities of pollen grains from specific genotypes and cultivars are important and useful for taxonomy, phylogeny, palaeobotany, breeding programmes, e.g., pear (Westwood and Challice, 1978), grape (Ahmedullah, 1983), sweet cherry (Miaja et al, 2000), apricot (Arzani et al, 2005), cornelian cherry (Mert, C. 2009), persimmon , hazelnut (Nikolaieva et al, 2014), jujube (Rouhakhsh, et al, 2014), and chestnut (Grygorieva et al, 2015).…”
Section: Introductionmentioning
confidence: 99%